The comparison of the efficacy of social skills group training ,stress inoculation training on psychological well-being of post troaumatic stress disorder(P.T.S.D)veteran\'s son. - M. esmaeili; M. Kalantari; K. Askari; H. Molavi; S. Mahdavi (Afarand Scholarly Publishing Institute, 2011)
Abstract Background: Despite the existence of a large volume of literature and research on psychological well-being (PWB) of the general population, very few studies have focused on post traumatic stress disorder (P. T. S. D) veteranschr('39') family. Purpose: The aim of the present research was to compare the effectiveness of social skills group training and stress Inoculation Training (SIT) on psychological well-being of post traumatic stress disorder veteranschr('39') son. Method & materials: In order to administer this study, 45 veteranschr('39') son were selected randomly from 14-18 years high school children population of Isfahan city via random cluster sampling method and assigned randomly to two experimental and one control group (each group consist of 15 adolescence). The design of the study was comparative experimental and control groups in pretest , post test and after 4 month follow up. The intervention were social skills group training and stress Inoculation Training. The instruments were psychological well-being of Borumand and Molavi, Ryff 's psychological well-being and demographical information questionnaires. data was analyzed by Multivariate Covariance analysis of variance. Results & conclusion: Findings indicate that social skills group training stress Inoculation Training can improve psychological well-being of son's veterans with post traumatic stress disorder (P. T. S. D). Stress Inoculation Training was more effective and efficient than social skills group training.